Kedudukan Undang-Undang No.11 Tahun 2020 tentang Cipta Kerja Pasca Pemberlakuan serta Pengaruhnya pada Bidang Kesehatan - Litya Surisdani Anggraeniko; Marlia Hafny Afrilies (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The employment introduction circumstance has brought superiorities and deprivations in indefinite fields. In the wellness sector, e.g., many inconsistencies chalk up been constitute with wellness collection no. 36 of 2009 and the collection on wellness working man No. 36 of 2014. The disposition euphemistic pre-owned is touchstone and legal. The emanations discussed are how the substitutions in the wellness sphere in the collection on Manpower modifications change, and how the collection on Manpower modifications make an analogy with with the wellness collection and the wellness Manpower circumstance for analysis. finally, in the collection on employment introduction related wellness services, the wellness sphere has identified many substitutions and if many existences over-the-counter than wellness working man and examination facilitate personnel. moreover, the three-year infirmary licensing transaction is anticipated to come around the superiority of utilities if by medical centre to the agreement thanks to the superiority of utilities has not changed. moreover, it was constitute that many percentages of the collection were not in conformation with collection No. 36 on wellness of 2009 and collection No. 36 of wellness working man of 2014These contents had existed before, causing new distortions and deviations. Keyword: Judicial Review, Omnibus Law, health